Resistência à mudança organizacional: correlatos valorativos e organizacionais - Nascimento, Dayse Ayres Mendes do (2012)
The aim of this dissertation was to develop an explanatory model of the resistance to organizational change, taking as independent variables the organizational climate and human values, considering the self-perceived performance as the variable to be explained in the model. Study 1 aimed at verifying the psychometric properties of the measures of resistance to change, self-perceived performance and organizational climate. Participants were 306 employees from a private company of João Pessoa (PB). These had mean age of 28 years (sd = 7.38), being mostly male (77.5%). They answered five instruments: Resistance to Change Scale, Organizational Climate Scale, Basic Values Survey, Self-perceived Performance Scale and demographic information, which were used in the subsequent studies. Results indicated satisfactory psychometric properties of the instruments, allowing the use to reach the objective of the present dissertation. Study 2 aimed at knowing the correlation between the variables resistance to change, organizational climate, human values and self-perceived performance, seeking to structure the explanatory model of resistance to change. Participants were 240 employees from two public companies and one private from Paraíba, with mean age of 38 years (sd = 12.42), and being mostly female (56.7%). Three models were developed: the first (M1) with the direct influence of organizational climate (posture of the leadership and pleasant environment) and of idealist values in the resistance to change and of this in the self-perceived performance; the second model (M2), in the same direction of the first, but with the organizational climate influencing directly the self-perceived performance; and, finally, the third model (M3), also in the same direction of the second, but with de direct influence of idealist values in the self-perceived performance. Results indicated the M2 as more satisfactory, presenting adequate fit indexes. Study 3 aimed to test the models developed in the previous study. Participants were 227 employees from a public company of João Pessoa (PB), which has unities in the country of the state. They had mean age of 40 years (sd = 10.45) and mostly were male (83.3%). Unlike the Study 2, in this the M3 was the more adequate, in which organizational climate and idealist values influence directly in the self-perceived performance. Finally, the Study 4 replicated the three developed models, and the more adequate was the one produced in Study 3. The final product of this dissertation was the development of the theoretical model values/organizational climate - resistance to organizational change - selfperceived performance. Thus, after the elaboration, testing and replication of the model, we have organizational climate and human values as explanatory variables of the resistance to change and the influence of this in the self-perceived performance. Therefore, it is understood that a positive perception from the employee about his work environment, specially concerning the posture of the leadership and the pleasant environment, influence the attitude of resisting or not to changing. Similarly, individuals guided by idealist values tend to resist less to the process of changing. Furthermore, organizational climate, idealist values and resistance to change have a direct impact on the individual s perception about his performance.